2017
DOI: 10.1093/wber/lhx007
|View full text |Cite
|
Sign up to set email alerts
|

Migration and Cross-Border Financial Flows

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…Likewise, it is argued that immigrants help promote private cross-border financial flows, offshoring, and foreign direct investment (FDI) by providing relevant information, reducing uncertainty and building trust (see, e.g. Leblang, 2010;Javorcik et al, 2011;Kugler et al, 2013).…”
Section: Why Remittances Matter For Aid Effectsmentioning
confidence: 99%
See 3 more Smart Citations
“…Likewise, it is argued that immigrants help promote private cross-border financial flows, offshoring, and foreign direct investment (FDI) by providing relevant information, reducing uncertainty and building trust (see, e.g. Leblang, 2010;Javorcik et al, 2011;Kugler et al, 2013).…”
Section: Why Remittances Matter For Aid Effectsmentioning
confidence: 99%
“…8 Furthermore, compared with the effects of migration on international trade and private financial flows, it appears to be more difficult to reduce "information and trust friction" when it comes to the effectiveness of official development aid. According to the literature on trade and FDI, it is mainly skilled migrants who play a significant role in fostering private international flows (Head and Ries, 1998;Javorcik et al, 2011;Kugler et al, 2013). However, migrants and temporary workers from strongly aid-dependent countries are often unskilled and may lack the knowledge and contacts needed for reducing transaction costs.…”
Section: Why Remittances Matter For Aid Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…When it comes to trade, several studies have shown that migrants play an important role in reducing non-tariff barriers between nations (e.g., Gould, 1994;Rauch, 1999;Rauch and Trindade, 2002;Cohen et al, 2017;Parsons and Vézina, 2018 A similar argument is made for cross-borders investment, which is often hindered by risks associated with the uncertainty on formal and informal rules in the "other" country. Migration has been proved to help mitigate those risks by liaising between potential investors and partners, both private and public, as it has been shown empirically by several studies (e.g., Kugler and Rapoport, 2007;Javorcik et al, 2011;Foley and Kerr, 2013;Burchardi et al, 2018;Kugler et al, 2018;Mayda et al, 2020).…”
Section: Business and Information Networkmentioning
confidence: 99%